Robert SPENCE. A Functional Approach to Translation Studies: New systemic linguistic challenges in empirically informed didactics. Berlin: dissertation.de. 2004. 286 pp. ISBN 3-89825-777-0 - Hüsgen, Thomas J.C. (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
.